Alunos com altas habilidades/superdotação e o fenômeno bullying - Maciel, Miriam de Oliveira (2012)
Students with High Abilities/Giftedness (HA/G) are not often identified and thus are not recognized, nor had their potential valued in school and family environments. This is due to various myths and misconceptions that society specifically the school community (teachers, parents, and classmates) has about HA/G. However, violence in schools is increasing significantly and one of its most common forms is Bullying. This phenomenon occurs when the physical, psychological, veiled or not, happen repeatedly with the same victim. In this sense, students with HA/G can guide their potential to non-constructive ways, if not recognized and encouraged. However, due to the prevailing myths about HA/G, these individuals can be victimized because they are characterized often as nerds, geeks, and asskisser of teachers, among other stereotypes. In this perspective, there is an issue to be investigated: "Bullying at school is related to recognition lack of students potential with High Abilities/Giftedness?" To answer this question, the Research Project "Students with High Abilities/Giftedness and Bullying Phenomenon" aims mainly to study the relationship between the recognition lack of students with HA/G and bullying behavior in schools, in order to understand whether there is influence of potential recognition absence for hostile behavior construction among classmates. For this purpose, the methodology used is based on exploratory research descriptive, since this type of research gives researchers the description of phenomena and their possible relationships. This research approach is qualitative, whereas the data collection instruments become possible the discovery of the number of students involved in bullying phenomenon, the number of students with HA/G, and the number of students who exhibit both characteristics. The results provided an understanding that nonrecognition and no appreciation of students with HA/G promote their involvement with the Bullying Phenomenon, pointing to the prevalence of their potentials manifesting through violence. In addition, teachers and family often ignore and/or promote no appreciation and disrespect for these children. Finally, with this research, it is expected that academic community understand the specific learning needs of students with HA/G, in order to recognize and value their potential, and to adopt measures to anti-bullying phenomenon.